If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1p + 5 = 25 + -6p Reorder the terms: 5 + -1p = 25 + -6p Solving 5 + -1p = 25 + -6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '6p' to each side of the equation. 5 + -1p + 6p = 25 + -6p + 6p Combine like terms: -1p + 6p = 5p 5 + 5p = 25 + -6p + 6p Combine like terms: -6p + 6p = 0 5 + 5p = 25 + 0 5 + 5p = 25 Add '-5' to each side of the equation. 5 + -5 + 5p = 25 + -5 Combine like terms: 5 + -5 = 0 0 + 5p = 25 + -5 5p = 25 + -5 Combine like terms: 25 + -5 = 20 5p = 20 Divide each side by '5'. p = 4 Simplifying p = 4
| -5(k-3)=-90 | | 3g+17=5 | | .75*80= | | 2-x=-5(x-2) | | 4f-3=13 | | -3+2x=-(4-x) | | 2sin(x)-3=-2 | | 5d-7=23 | | 7=2x^2+6x+7 | | -3(5+3x)=4x-2 | | B+8=1 | | -.7x+26.9=-x+29 | | 10-x+6x=-x-4x | | -22=-6+k | | 24+8x=40 | | X^2+kx-k+8=0 | | -22=-6+6 | | 3(x+6)=2(3x+15) | | -7x+26.9=-x+29 | | 1in=6ft | | 10(b-8)-4+3b= | | 3c-1=20 | | 6+3x=-12-4x | | 3X+4=5Y+1 | | 3(x+2)-12=5(x+1) | | 11-4x=6-5x+4 | | 9xy-13=40 | | 3y+84=7x | | 6(-3b-3)+6=-120 | | 9x+7(x+12)=-6x-9(2x+4) | | log(x)-0.5(log(x+4))-1=0 | | 1.39lnx=0.014 |